Membership Interests in a Limited Liability Company - Nikolić, Dušan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2024)
The author analyzes the notion of membership interests in a limited liability company under Serbian law. Membership interests in a limited liability company represent one of the most significant notions characterizing the entire form of a limited liability company. Considering the scope of the membership interests’ notion, the analysis is divided into three sections at the beginning of the analysis. The first section addresses basic terminological and conceptual considerations. The second deals with issues of the legal nature of membership interests, while the third includes an analysis of principles related to membership interests. Regarding the legal nature of membership interests, special emphasis is placed on examining the nature of membership interests in comparison with the related notion of shares in joint-stock companies and the legal notion of digital assets. Finally, the nature of membership interests is also analyzed from the perspective of property law. In the final section, the principles of proportionality and will autonomy that shape the concept of membership interests are presented, followed by an analysis of their application in current positive law. The conclusions from the analysis of certain open questions within the notion of membership interests should serve as a basis for future improvements of this legal notion, particularly in the part relating to the application of the will autonomy principle.